Em nome da república: escolas e tradições modernas - Moreira, Keila Cruz (2011)
Our research aims to analyze some institutions of primary education in so-called First Republic in Natal/RN, when they were considered high standard institutions on training, dissemination and creation of national identity and republican traditions. Thus, we investigated to try to understand the creation of the new man and the invention of new traditions to confirm the status of republican modernity in two schools in Natal, the Colegio Americano, a private one, and a standard model of school, Augusto Severo, which is a public one. As a basis we have the history of institutions to analyze, paying close attention to consider the use of imitation in cultural patrimony as well as the use of strategies to distinguish. The concept of ownership follows, for present purposes, their focus of study on observation of diverse and contrasting use of these cultural objects, texts, readings and ideas from research institutions. For analysis of the link which occurs within the school environment, in every period of its history, we used the concept of school culture as a set of rules and practices which define knowledge to teach and conduct the introject. A culture that incorporates the school to keep a set with other religious cultures, political and popular of its time and space. In this sense, the educational institutions which we studied while showing what kind of in this work by preparing cultures, codes, different practices, and specific individuals they have, they were in important locations to provide modern cultural appropriation as a strategy for educational innovation and a factor of rationality and efficiency which could be observed and controlled, so gradually the modern school education was organized to produce its own society. As a challenge of affirmation and incorporating diverse social experiences to produce the modern, civilized man of the Republican time, the school, as part of the social life, which is singular in its practices, not only the set of reforms, decrees, laws and projects, but also as expressions of concept about life and society in terms of material, symbolic and cultural symbols in the social context in modernization. We focused on these two schools, because inside the wide cultural and material status of the city, they were the first republic schools which had the goal of having men and woman together culturally , with a view to adapting them to the modern movement to make them civilized / educated / rational . On this view, we would emphasize that this statement needs a reinvention as a new way through what is made at the schools which production of new spaces, practices, rites and what represents school, making and expressing a new identity, modern, different of the old symbols of the Empire. For this, nothing better than the organization of schooling, emphasizing on educating the individual and his/her responsibilities with the order and progress. We need to understand the past as a result of conflicts, including strengths and limitations within the historical and social context, and the invention of tradition as a process of formalization and ritualization of acts which want to perpetuate, as a reference to a group identity. These are practices and social educative representations which support the understanding of pedagogical and educational ideas at this historical moment, making a new way of being and doing in the Republican universe